Alloy roller and surface strengthening treatment method thereof

By using ductile iron as the roller core material and high chromium element alloy composition as the external working layer in the alloy roll, and applying reinforced alloy powder on the external working layer, the problem that the alloy roll cannot have high strength, high toughness and high temperature resistance is solved, which significantly improves the hardness and wear resistance of the roll and extends the service life.

CN119710438APending Publication Date: 2025-03-28JIANGSU GONGCHANG ROLL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411869937.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing alloy rolls cannot have high strength, high toughness and high temperature resistance, which leads to easy friction and wear, mechanical fatigue, thermal fatigue and oxidation during the rolling process, thereby shortening the service life of the rolling roller.

Method used

An alloy composition containing high chromium elements is used with ductile iron as the roller core material and an alloy composition containing high chromium elements on the outer working layer, and a reinforcing alloy powder is applied to the outer working layer to form a microcapsule phase change material with a core-shell structure to improve the high temperature resistance and heat storage properties of the rollers.

Benefits of technology

Through this method, the hardness and wear resistance of the alloy rolls are significantly improved, which can better resist high temperatures and heat storage, extend the service life of the rolls and reduce working losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005195507220000131
    Figure BDA0005195507220000131
Patent Text Reader

Abstract

The invention discloses an alloy roller and a surface strengthening treatment method thereof, belongs to the technical field of rollers, and aims to solve the technical problem that a composite alloy roller prepared in the prior art cannot have high strength, high toughness and high temperature resistance at the same time. The alloy roller sequentially comprises a core part, an external working layer and a reinforced alloy powder coating from inside to outside, the core part is made of nodular cast iron and comprises carbon, silicon, manganese, nickel, chromium, molybdenum, magnesium and iron which are specific components, the external working layer comprises carbon, chromium, iron, aluminum, rare earth elements and iron which are specific components, and the core part and the external working layer are manufactured through a specific machining technology. The high-strength and high-toughness composite alloy roller is prepared, the exterior of the composite alloy roller is subjected to a surface strengthening treatment method, that is, laser spraying is adopted for strengthening alloy powder, the high temperature resistance of the alloy roller is improved, and the strengthening alloy powder is formed by secondary coating of a molten salt material through a chemical nickel plating solution to obtain microcapsules of a core-shell structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rolling rollers, and in particular to an alloy rolling roller and a surface strengthening treatment method thereof. Background Art

[0002] Rollers are the main processing components that cause metal to undergo plastic deformation. They are composed of a roll body and a roll neck. During the rolling process, the huge friction between the material being rolled and the rolls pulls the material into the rolls rotating in different directions, causing it to undergo plastic deformation. After the material passes through the rolls, under alternating hot and cold conditions, the rolls will produce greater thermal fatigue stress, causing the roll surfaces to suffer from friction wear, mechanical fatigue, thermal fatigue, and oxidation. Therefore, rolls have always been the main consumable components in the metallurgical industry. How to improve the strength, toughness, and high temperature resistance of rolls, thereby further increasing the service life of alloy rolls, is a technical issue that needs to be addressed urgently.

[0003] Patent application CN114570903A discloses a method for preparing a wear-resistant low-alloy high-speed steel composite roller, which comprises casting a roller sleeve with low-alloy high-speed steel, and hot-fitting and compounding it with a medium-carbon steel roller shaft through mechanical processing and heat treatment processes to obtain a composite roller with good wear resistance and mechanical properties; however, the high temperature resistance and heat storage performance of the above-mentioned composite roller are not good, and how to strengthen the outer surface of the roller to improve the high temperature resistance and heat storage performance of the composite roller is still a process that needs further exploration; in addition, although the raw material composition of the above-mentioned low-alloy high-speed steel has achieved the advantages of green recycling, its raw material composition and ratio are not the optimal ratio for improving the strength and toughness of the roller.

[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0005] The object of the present invention is to provide an alloy rolling roll and a surface strengthening treatment method thereof, so as to solve the technical problem that the alloy rolling roll prepared in the prior art cannot have high strength, high toughness and high temperature resistance.

[0006] The object of the present invention can be achieved by the following technical scheme: an alloy roller, which comprises a core, an outer working layer and a reinforced alloy powder coating from the inside to the outside, the core and the outer working layer are connected to obtain a composite alloy roller, and the composite alloy roller is coated with reinforced alloy powder to obtain a reinforced alloy powder coating;

[0007] The outer working layer comprises the following elements in weight percentage: 2.7-3%wt of carbon, 15-20%wt of chromium, 4-5%wt of iron, 0.2-0.3%wt of aluminum, 0.02-0.05%wt of rare earth lanthanum, and the remainder is iron and other inevitable impurities;

[0008] The core is ductile iron, which includes the following elements in weight percentage: 3.3-3.5%wt of carbon, 1.4-2.2%wt of silicon, 0.5-0.8%wt of manganese, 3.5-4.5%wt of nickel, 0.5-1.5%wt of chromium, 0.2-0.3%wt of molybdenum, 0.04-0.05%wt of magnesium, and the remainder is iron and other inevitable impurities.

[0009] Furthermore, the method for preparing the composite alloy roll comprises the following steps:

[0010] B1. Carbon, silicon, manganese, nickel, chromium, molybdenum, magnesium and iron are used as chemical components and proportioned according to mass fraction to obtain a material composition, the material composition is ball-milled to obtain an alloy powder, and the alloy powder is post-processed to obtain a composite material;

[0011] B2. Add the composite material into a medium frequency induction furnace for smelting at a smelting temperature of 2000-2100° C. to obtain a molten metal. Before being taken out of the furnace, the molten metal is kept warm in this smelting temperature range for 5-10 minutes, and then poured into a steel ingot mold to cast into 50 mm ductile iron;

[0012] B3. A cylindrical metal casting film with an inner wall of φ100 mm is used as a container. The cylindrical metal casting film is placed in a vacuum induction furnace. Carbon, chromium, titanium, aluminum, rare earth lanthanum and iron are used as chemical components and proportioned according to mass fractions. The mixture is melted to obtain molten metal liquid. The molten metal liquid is then poured into the cylindrical metal casting film using a double-hole riser to obtain a composite alloy rolling mill roll.

[0013] Furthermore, in step B1, during ball milling, the ball-to-material ratio is 5:1, and the ball milling speed is 12h / 500rpm; the post-processing includes: adding the alloy powder into the mold, cold pressing at a pressure of 200t, and then maintaining the pressure for 1-2min; heating the mold to 450°C and maintaining it for 1h under argon protection, and then maintaining it at 850°C for 2-5min, and extruding it with a pressure of 200t to obtain a composite material.

[0014] Furthermore, the method for preparing the reinforced alloy powder comprises the following steps:

[0015] A1, potassium carbonate, sodium carbonate and lithium carbonate are uniformly mixed in a mass ratio of 35:33:32 to obtain an inorganic mixture, the inorganic mixture is ball-milled to obtain an inorganic mixture powder; the inorganic mixture powder is calcined at a high temperature to obtain a molten salt material;

[0016] A2, the molten salt material and ethanol are mixed at a solid-liquid ratio of 1:15-20 to obtain a mixture; the mixture is then subjected to ultrasonic treatment using an ultrasonic crusher to obtain a suspension; the coating material is added to the above suspension, mixed and stirred at 100-200r / min at room temperature for 24h, and then washed with anhydrous ethanol and centrifuged to remove excess coating material to obtain a coated molten salt material;

[0017] A3. The pH value of the plating solution is adjusted to 4.5-5.5, and the modified molten salt particles are added to the plating solution to carry out primary reaction and secondary reaction in sequence, and then vacuum dried at 120-130° C. to constant weight to obtain reinforced alloy powder.

[0018] Furthermore, in step A1, the ball milling speed is 100-200r / min, and the ball milling time is 10-15h; the high-temperature calcination temperature is 450-500°C, and the high-temperature calcination time is 30-60min; in step A2, the coating material is polyvinyl pyrrolidone; the frequency of ultrasonic treatment is 1000-2000Hz, and the duration of ultrasonic treatment is 30-60min; the mass ratio of the mixture to the coating material is 5:1-2.

[0019] Furthermore, in step A3, the dosage ratio of the modified molten salt particles and the plating solution is 100g:10-20mL; the temperature of the primary reaction is 50-60°C, and the duration of the primary reaction is 30-60min; the temperature of the secondary reaction is 80-90°C, and the duration of the secondary reaction is 30-60min.

[0020] The present invention also provides a surface strengthening treatment method for an alloy roll, comprising the following steps:

[0021] S1. The reinforced alloy powder and the binder are mixed evenly to obtain a powder, and the powder is evenly coated on the surface of the composite alloy roller, with a coating thickness of 0.3-0.5 mm, and the coating is naturally air-dried and heat-insulated to obtain a coated alloy roller;

[0022] S2. The coated alloy roll is preheated to 100-200° C. to obtain a preheated alloy roll. The preheated alloy roll is fixed on a sample holder of a PRC-3000 fast axial flow CO2 laser and subjected to laser treatment to obtain an alloy roll.

[0023] Furthermore, in step S1, the binder is polyvinyl alcohol, and the mass ratio of the reinforced alloy powder to the binder is 1:1; in step S2, during the laser treatment, nitrogen protection is used on the side; the laser spot diameter is 2 mm, the laser power is 1500-2000 W, and the laser scanning speed is 1500-2000 mm / min.

[0024] The present invention has the following beneficial effects:

[0025] 1. The alloy roll cast by the present invention comprises a roll core material, an outer working layer and a reinforced alloy powder coating from the inside to the outside, and uses ductile iron that meets the toughness requirements as the roll core material, and an alloy composition with high hardness and high wear resistance as the outer working layer; the outer working layer and the roll core material are compounded by melt casting, and then the reinforced alloy powder is coated on the surface of the outer working layer to obtain a reinforced alloy powder coating to form an alloy roll; the outer working layer greatly increases the content of chromium compared to the core part, and the chromium element will not only form eutectic M7C3 carbide, but also dissolve a part of chromium in the matrix, so that the stability of austenite is improved, thereby improving the hardness and wear resistance of the working layer material; a small amount of aluminum is added to the outer working layer to purify the molten iron, and a trace amount of rare earth element lanthanum is added to the outer working layer, which can be adsorbed on the surface of primary austenite dendrites to hinder their continued growth, thereby causing the carbides to be refined and tend to be isolated and distributed, thereby improving the strength and toughness of the outer working layer; the roll core material of the alloy roll further adjusts the carbon-chromium ratio, and magnesium and molybdenum with high toughness are added.

[0026] 2. A reinforced alloy powder coating is applied to the outer working layer of the alloy roller. The reinforced alloy powder coating is essentially a microcapsule phase change material with a core-shell structure, and its core layer is a mixture of high-temperature phase change heat storage materials such as potassium carbonate, sodium carbonate and lithium carbonate. The high-temperature phase change heat storage material has the advantages of high phase change energy density, high phase change temperature and small volume change during solid-liquid phase change, which can further improve the high temperature resistance and high heat storage capacity of the alloy roller. However, the above-mentioned molten salt material may be corrosive to the alloy roller to a certain extent, so the molten salt particles are coated twice with chemical nickel plating solution to form a microcapsule phase change material with a two-layer core-shell structure.

[0027] 3. The core of the alloy roller is formulated according to the chemical composition to obtain a material composition, which is then subjected to a series of process treatments to be cast into ductile iron with a diameter of 50 mm, and then the external working layer material is melted to obtain molten metal liquid; a double-hole riser casting method is adopted to cast it to the outside of the core to obtain a composite alloy roller with an inner and outer diameter ratio of 1:1, and polyvinyl alcohol is used as a binder to obtain a powder by mixing it with a reinforcing alloy powder. The powder is coated on the outside of the composite alloy roller, and then subjected to laser treatment. The alloy roller is prepared by the above-mentioned surface strengthening treatment method. The alloy roller prepared by the present invention has the properties of high strength, high toughness and high temperature resistance, thereby being able to reduce the working loss of the alloy roller and extend the service life of the alloy roller itself. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a method for preparing a composite alloy roll for an alloy roll, comprising the following steps:

[0031] B1. The core of the alloy roll is ductile iron, which includes the following elements in weight percentage: 3.3%wt of carbon, 1.4%wt of silicon, 0.5%wt of manganese, 3.5%wt of nickel, 0.5%wt of chromium, 0.2%wt of molybdenum, 0.04%wt of magnesium, and the remainder is iron and other inevitable impurities.

[0032] The above chemical components were mixed according to the corresponding mass fractions to obtain a material composition, and the material composition was added to a ball mill for ball milling, with a ball-to-material ratio of 5:1 and a ball milling speed of 12h / 500rpm to obtain an alloy powder. The alloy powder was added to a φ50mm mold, cold pressed at a pressure of 200t, and then kept under pressure for 1min; the mold was heated to 450℃ and kept warm for 1h under argon protection, and the sample was heated to 850℃ and kept warm for 2min through an induction coil, and extruded at a pressure of 200t to obtain a composite material.

[0033] B2. Select a medium frequency induction furnace with a capacity of 10Kg, a rated power of 50KW, an output power of 2500Hz, and a cooling tower water flow rate of 3m 3 / h. The composite material is added into the medium frequency induction furnace for smelting at a smelting temperature of 2000°C. The molten metal is kept in this temperature range for 5 minutes before being taken out of the furnace. At the same time, aluminum wire is added to deoxidize the molten metal. After the molten metal is kept in temperature, it is taken out of the furnace and poured into a steel ingot mold to be cast into 50mm ductile iron.

[0034] B3. Select a cylindrical metal casting film as a container, the inner wall of the casting film is φ100mm and the wall thickness is 20mm; put ductile iron into the cylindrical metal casting film, and then put the cylindrical metal casting film into a vacuum induction furnace.

[0035] B4. The outer working layer of the alloy roll includes the following elements in weight percentage: 2.7%wt carbon, 15%wt chromium, 4%wt titanium, 0.2%wt aluminum, 0.02%wt rare earth lanthanum, and the remainder is iron and other inevitable impurities. The above chemical components are batched and melted according to the mass fraction to obtain molten metal. Then, the molten metal is poured into a cylindrical metal mold using a double-hole riser. The vacuum degree in the furnace is maintained at 2Pa, and the pouring time is 20s to obtain a composite alloy roll.

[0036] Example 2

[0037] This embodiment provides a method for preparing a composite alloy roll for an alloy roll, comprising the following steps:

[0038] B1. The core of the alloy roll is ductile iron, which includes the following elements in weight percentage: 3.3-3.5%wt of carbon, 1.8%wt of silicon, 0.6%wt of manganese, 4%wt of nickel, 1%wt of chromium, 0.25%wt of molybdenum, 0.045%wt of magnesium, and the remainder is iron and other inevitable impurities.

[0039] The above chemical components were mixed according to the corresponding mass fractions to obtain a material composition, and the material composition was added to a ball mill for ball milling, with a ball-to-material ratio of 5:1 and a ball milling speed of 12h / 500rpm to obtain an alloy powder. The alloy powder was added to a φ50mm mold, cold pressed at a pressure of 200t, and then kept under pressure for 1min; the mold was heated to 450℃ and kept warm for 1h under argon protection, and the sample was heated to 850℃ and kept warm for 2min through an induction coil, and extruded with a pressure of 200t to obtain a composite material.

[0040] B2. Select a medium frequency induction furnace with a capacity of 10Kg, a rated power of 55KW, an output power of 2600Hz, and a cooling tower water flow rate of 4m 3 / h. The composite material is added into the medium frequency induction furnace for smelting at a smelting temperature of 2050°C. The molten metal is kept in this temperature range for 8 minutes before being taken out of the furnace. At the same time, aluminum wire is added to deoxidize the molten metal. After the molten metal is kept in temperature, it is taken out of the furnace and poured into a steel ingot mold to be cast into 50mm ductile iron.

[0041] B3. Select a cylindrical metal casting film as a container, the inner wall of the casting film is φ100mm and the wall thickness is 20mm; put ductile iron into the cylindrical metal casting film, and then put the cylindrical metal casting film into a vacuum induction furnace.

[0042] B4. The outer working layer of the alloy roll includes the following elements in weight percentage: 2.8%wt carbon, 17%wt chromium, 4%wt titanium, 0.25%wt aluminum, 0.04%wt rare earth lanthanum, and the remainder is iron and other inevitable impurities. The above chemical components are batched and melted according to the corresponding mass fractions to obtain molten metal. Then, the molten metal is poured into a cylindrical metal mold using a double-hole riser. The vacuum degree in the furnace is maintained at 2Pa, and the pouring time is 25s to obtain a composite alloy roll.

[0043] Example 3

[0044] This embodiment provides a method for preparing a composite alloy roll for an alloy roll, comprising the following steps:

[0045] B1. The core of the alloy roll is ductile iron, which includes the following elements in weight percentage: 3.5%wt of carbon, 2.2%wt of silicon, 0.8%wt of manganese, 4.5%wt of nickel, 1.5%wt of chromium, 0.3%wt of molybdenum, 0.05%wt of magnesium, and the balance is iron and other inevitable impurities.

[0046] The above chemical components were mixed according to the corresponding mass fractions to obtain a material composition, and the material composition was added to a ball mill for ball milling, with a ball-to-material ratio of 5:1 and a ball milling speed of 12h / 500rpm to obtain an alloy powder. The alloy powder was added to a φ50mm mold, cold pressed at a pressure of 200t, and then kept under pressure for 2min; the mold was heated to 450℃ and kept warm for 1h under argon protection, and the sample was heated to 850℃ and kept warm for 5min through an induction coil, and extruded at a pressure of 200t to obtain a composite material.

[0047] B2. Select a medium frequency induction furnace with a capacity of 10Kg, a rated power of 60KW, an output power of 3000Hz, and a cooling tower water flow rate of 5m 3 / h. The composite material is added into the medium frequency induction furnace for smelting at a smelting temperature of 2100°C. The molten metal is kept in this temperature range for 10 minutes before being taken out of the furnace. At the same time, aluminum wire is added to deoxidize the molten metal. After the molten metal is kept in temperature, it is taken out of the furnace and poured into a steel ingot mold to be cast into 50mm ductile iron.

[0048] B3. Select a cylindrical metal casting film as a container, the inner wall of the casting film is φ100mm and the wall thickness is 20mm; put ductile iron into the cylindrical metal casting film, and then put the cylindrical metal casting film into a vacuum induction furnace.

[0049] B4. The outer working layer of the alloy roll includes the following elements in weight percentage: 3%wt carbon, 20%wt chromium, 5%wt titanium, 0.3%wt aluminum, 0.05%wt rare earth lanthanum, and the remainder is iron and other inevitable impurities. The above chemical components are batched and melted according to the corresponding mass fractions to obtain molten metal. Then, the molten metal is poured into a cylindrical metal mold using a double-hole riser. The vacuum degree in the furnace is maintained at 2Pa, and the pouring time is 30s to obtain a composite alloy roll.

[0050] Example 4

[0051] This embodiment provides a method for preparing a reinforced alloy powder for an alloy roller, comprising the following steps:

[0052] A1. Potassium carbonate, sodium carbonate and lithium carbonate are mixed uniformly in a mass ratio of 35:33:32 to obtain an inorganic mixture. The inorganic mixture is added to a ball mill, and anhydrous ethanol is used as a ball milling medium for ball milling at a ball milling speed of 100 r / min for 10 hours to obtain an inorganic mixed powder; the inorganic mixed powder is then added to a muffle furnace for high-temperature calcination at a temperature of 450°C for 30 minutes to obtain a molten salt material.

[0053] A2, the molten salt material and ethanol were mixed at a solid-liquid ratio of 1:15 to obtain a suspension. The suspension was subjected to ultrasonic treatment using an ultrasonic crusher, the frequency of the ultrasonic treatment was 1000 Hz, and the duration of the ultrasonic treatment was 30 min.

[0054] A3. According to the weight parts, 0.5 parts of the coating material polyvinyl pyrrolidone was added to 20 parts of the suspension. The suspension was mixed and stirred at 100 r / min at room temperature for 24 hours, and then centrifuged to remove excess coating material to obtain modified molten salt particles.

[0055] A4. Adjust the pH value of the chemical nickel plating solution to 4.5, add the modified molten salt particles to the chemical nickel plating solution for reaction at a temperature of 50°C for 30 minutes, and then filter to obtain plated particles; add the plated particles to the chemical nickel plating solution for secondary reaction at a temperature of 80°C for 30 minutes, and then filter to obtain solids. In the primary and secondary reactions, the solid-liquid ratio of the modified molten salt particles and the chemical nickel plating solution is 1:3; place the solid in a vacuum drying oven, dry it at 120°C to constant weight, and then grind it to a particle size of 100μm to obtain a reinforced alloy composite material.

[0056] Example 5

[0057] This embodiment provides a method for preparing a reinforced alloy powder for an alloy roller, comprising the following steps:

[0058] A1. Potassium carbonate, sodium carbonate and lithium carbonate are mixed uniformly in a mass ratio of 35:33:32 to obtain an inorganic mixture. The inorganic mixture is added to a ball mill, and anhydrous ethanol is used as a ball milling medium for ball milling. The ball milling speed is 150r / min, and the ball milling time is 12h to obtain an inorganic mixed powder; the inorganic mixed powder is then added to a muffle furnace for high-temperature calcination. The high-temperature calcination temperature is 480°C, and the high-temperature calcination time is 50min to obtain a molten salt material.

[0059] A2, the molten salt material and ethanol were mixed at a solid-liquid ratio of 1:18 to obtain a suspension. The suspension was subjected to ultrasonic treatment using an ultrasonic crusher, the frequency of the ultrasonic treatment was 1500 Hz, and the duration of the ultrasonic treatment was 50 min.

[0060] A3. According to parts by weight, 1 part of the coating material polyvinyl pyrrolidone is added to 20 parts of the suspension, the suspension is mixed and stirred at 150 r / min at room temperature for 24 hours, and then centrifuged to remove excess coating material to obtain modified molten salt particles.

[0061] A4. Adjust the pH value of the chemical nickel plating solution to 5, add the modified molten salt particles to the chemical nickel plating solution for reaction, the reaction temperature is 55°C, the reaction time is 400 minutes, and then filter to obtain the plated particles; add the plated particles to the chemical nickel plating solution for secondary reaction, the temperature of the secondary reaction is 85°C, the secondary reaction time is 40 minutes, and then filter to obtain a solid. In the primary reaction and the secondary reaction, the solid-liquid ratio of the modified molten salt particles and the chemical nickel plating solution is 1:4; place the solid in a vacuum drying oven, dry it at 125°C to constant weight, and then grind it to a particle size of 150μm to obtain a reinforced alloy composite material.

[0062] Example 6

[0063] This embodiment provides a method for preparing a reinforced alloy powder for an alloy roller, comprising the following steps:

[0064] A1. Potassium carbonate, sodium carbonate and lithium carbonate are mixed uniformly in a mass ratio of 35:33:32 to obtain an inorganic mixture. The inorganic mixture is added to a ball mill, and anhydrous ethanol is used as a ball milling medium for ball milling at a ball milling speed of 200 r / min for 15 hours to obtain an inorganic mixed powder; the inorganic mixed powder is then added to a muffle furnace for high-temperature calcination at a temperature of 500° C. for 60 minutes to obtain a molten salt material.

[0065] A2, the molten salt material and ethanol were mixed at a solid-liquid ratio of 1:20 to obtain a suspension. The suspension was subjected to ultrasonic treatment using an ultrasonic crusher, the frequency of the ultrasonic treatment was 2000 Hz, and the duration of the ultrasonic treatment was 60 min.

[0066] A3. According to parts by weight, 1.5 parts of the coating material polyvinyl pyrrolidone were added to 20 parts of the suspension. The suspension was mixed and stirred at 200 r / min at room temperature for 24 hours, and then centrifuged to remove excess coating material to obtain modified molten salt particles.

[0067] A4. Adjust the pH value of the chemical nickel plating solution to 5.5, add the modified molten salt particles to the chemical nickel plating solution for reaction at a temperature of 60°C for 60 minutes, and then filter to obtain plated particles; add the plated particles to the chemical nickel plating solution for secondary reaction at a temperature of 90°C for 60 minutes, and then filter to obtain solids. In the primary and secondary reactions, the solid-liquid ratio of the modified molten salt particles and the chemical nickel plating solution is 1:5; place the solid in a vacuum drying oven, dry it at 130°C to constant weight, and then grind it to a particle size of 200μm to obtain a reinforced alloy composite material.

[0068] Example 7

[0069] This embodiment provides a surface strengthening treatment method for an alloy roll, comprising the following steps:

[0070] S1. Reinforced alloy powder and binder polyvinyl alcohol are mixed uniformly in a mass ratio of 1:1 to obtain a powder; the powder is uniformly coated on the surface of the composite alloy roller prepared in Example 6 to obtain a coating with a coating thickness of 0.3 mm. After the coating is naturally dried in the air, it is kept warm for 12 hours to obtain a coated alloy roller.

[0071] S2. The coated alloy roll is preheated to 100°C to obtain a preheated alloy roll. The preheated alloy roll is fixed on a sample holder of a PRC-3000 fast axial flow CO2 laser and laser treated to obtain an alloy roll; during the laser treatment, nitrogen is blown sideways for protection, wherein the laser spot diameter is 2 mm, the laser power is 1500 W, and the laser scanning speed is 1500 mm / min.

[0072] Example 8

[0073] This embodiment provides a surface strengthening treatment method for an alloy roll, comprising the following steps:

[0074] S1. Reinforced alloy powder and binder polyvinyl alcohol are mixed uniformly in a mass ratio of 1:1 to obtain a powder; the powder is uniformly coated on the surface of the composite alloy roller prepared in Example 6 to obtain a coating with a coating thickness of 0.4 mm. After the coating is naturally dried in the air, it is kept warm for 18 hours to obtain a coated alloy roller.

[0075] S2. The coated alloy roll is preheated to 150°C to obtain a preheated alloy roll. The preheated alloy roll is fixed on a sample holder of a PRC-3000 fast axial flow CO2 laser and laser treated to obtain an alloy roll; during the laser treatment, nitrogen is blown sideways for protection, wherein the laser spot diameter is 2 mm, the laser power is 1800 W, and the laser scanning speed is 1800 mm / min.

[0076] Example 9

[0077] This embodiment provides a surface strengthening treatment method for an alloy roll, comprising the following steps:

[0078] S1. Reinforced alloy powder and binder polyvinyl alcohol are mixed uniformly in a mass ratio of 1:1 to obtain a powder; the powder is uniformly coated on the surface of the composite alloy roller prepared in Example 6 to obtain a coating with a coating thickness of 0.5 mm. After the coating is naturally dried in the air, it is kept warm for 24 hours to obtain a coated alloy roller.

[0079] S2. The coated alloy roll is preheated to 200°C to obtain a preheated alloy roll. The preheated alloy roll is fixed on a sample holder of a PRC-3000 fast axial flow CO2 laser and laser treated to obtain an alloy roll; during the laser treatment, nitrogen is blown sideways for protection, wherein the laser spot diameter is 2 mm, the laser power is 2000 W, and the laser scanning speed is 2000 mm / min.

[0080] Comparative Example 1

[0081] Compared with Example 3, in this comparative example, the modified molten salt particles are added to the chemical nickel plating solution only once for reaction to obtain a reinforced alloy powder coating.

[0082] Comparative Example 2

[0083] Compared with the alloy roll prepared in Example 9, magnesium and molybdenum are not added to the core of the alloy roll in this comparative example.

[0084] Comparative Example 3

[0085] Compared with the alloy roller prepared in Example 9, the alloy roller in this comparative example does not contain rare earth lanthanum in the outer working layer.

[0086] Performance Testing:

[0087] 1. The reinforced alloy powders prepared in Examples 4-6 and Comparative Example 1 were subjected to a melting-solidification cycle test at a temperature between 450° C. and 530° C. for 100 cycles.

[0088] Detection and analysis: In the entire cycle test, the reinforced alloy powders prepared in Examples 1-3 did not have shell fracture or cracks; in addition, in the above cycle test, the mass of the reinforced alloy powder did not change, and there was no leakage of the surface molten salt. However, in Comparative Example 1, since the modified molten salt particles only reacted once in the chemical nickel plating solution, the prepared reinforced alloy composite material was only coated once, so its own high temperature resistance and stability decreased, and the mass of the reinforced alloy powder was detected to be reduced.

[0089] 2. The hardness of the composite alloy rollers prepared in Examples 7-9 and Comparative Examples 2-3 was tested using a universal hardness tester, using the HV5 level for testing, and the holding time for each test was 5 seconds.

[0090] 3. The tensile strength of the composite alloy rollers prepared in Examples 7-9 and Comparative Examples 2-3 was tested using a tensile testing machine. The tensile test speed was 1.5 mm / min. The calculation formula for the elongation of the sample was:

[0091] A=(Lμ-L0 / L0)×100%

[0092] Among them, A represents the elongation at break of the tensile specimen after stretching, Lμ is the gauge length after stretching, and L0 is the original gauge length of the tensile specimen.

[0093] 4. The sliding friction and wear of the composite alloy rollers prepared in Examples 7-9 and Comparative Examples 2-3 were tested using a friction and wear tester. The sliding distance of the friction and wear test was 4 mm, the test load was set to 20 N, the frequency was set to 4 Hz, and the diameter of the bearing steel selected for the grinding ball material was 6 mm. Each friction and wear test was performed three times, and the average value of the weight loss was calculated.

[0094] 5. The impact toughness of the alloy rolls prepared in Examples 7-9 and Comparative Examples 2-3 was tested using an XJ-40A pendulum impact tester. The specific test results are shown in Table 1 below:

[0095] Table 1- Sample performance test data table

[0096]

[0097] Data Analysis:

[0098] A comparative analysis of the data in Table 1 shows that the alloy rollers prepared in Examples 7-9 of the present invention have higher mechanical properties, as shown by higher values ​​of hardness, tensile strength and sliding friction of the alloy rollers. However, in Comparative Example 3, rare earth lanthanum is not added to the outer working layer of the prepared alloy roller, which reduces its own mechanical properties, as shown by decreased hardness, tensile strength and friction and wear resistance of the alloy roller. In Comparative Example 2, magnesium and molybdenum are not added to the core of the prepared alloy roller, which reduces the impact toughness value of the prepared alloy roller.

[0099] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0100] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0101] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An alloy roll, characterized in that: The composite alloy roller comprises a core, an outer working layer and a reinforced alloy powder coating from the inside to the outside, the core and the outer working layer are connected to obtain a composite alloy roller, and the composite alloy roller is coated with reinforced alloy powder to obtain an alloy roller; The outer working layer comprises the following elements in weight percentage: 2.7-3%wt of carbon, 15-20%wt of chromium, 0.2-0.3%wt of aluminum, 0.02-0.05%wt of rare earth lanthanum, and the remainder is iron and other inevitable impurities; The core is ductile iron, which includes the following elements in weight percentage: 3.3-3.5%wt of carbon, 1.4-2.2%wt of silicon, 0.5-0.8%wt of manganese, 3.5-4.5%wt of nickel, 0.5-1.5%wt of chromium, 0.2-0.3%wt of molybdenum, 0.04-0.05%wt of magnesium, and the remainder is iron and other inevitable impurities.

2. An alloy roller according to claim 1, characterized in that: The method for preparing the composite alloy roller comprises the following steps: B1. Carbon, silicon, manganese, nickel, chromium, molybdenum, magnesium and iron are used as chemical components and proportioned according to mass fraction to obtain a material composition, the material composition is ball-milled to obtain an alloy powder, and the alloy powder is post-processed to obtain a composite material; B2. Add the composite material into a medium frequency induction furnace for smelting at a smelting temperature of 2000-2100° C. to obtain a molten metal; before being discharged from the furnace, the molten metal is kept in this smelting temperature range for 5-10 minutes, and then poured into a steel ingot mold to cast into 50 mm ductile iron; B3. A cylindrical metal casting film with an inner wall of φ100 mm is used as a container. The cylindrical metal casting film is placed in a vacuum induction furnace. Carbon, chromium, titanium, aluminum, rare earth lanthanum and iron are used as chemical components and proportioned according to mass fractions. The mixture is melted to obtain molten metal liquid. The molten metal liquid is then poured into the cylindrical metal casting film using a double-hole riser to obtain a composite alloy rolling mill roll.

3. An alloy roller according to claim 2, characterized in that: In step B1, during ball milling, the ball-to-material ratio is 5:1, and the ball milling speed is 12h / 500rpm; the post-processing includes: adding the alloy powder into the mold, cold pressing at a pressure of 200t, and then holding the pressure for 1-2min; heating the mold to 450°C and keeping it for 1h under argon protection, and then keeping it at 850°C for 2-5min, and extruding it with a pressure of 200t to obtain a composite material.

4. The alloy roll according to claim 1, characterized in that: The method for preparing the reinforced alloy powder comprises the following steps: A1, potassium carbonate, sodium carbonate and lithium carbonate are uniformly mixed in a mass ratio of 35:33:32 to obtain an inorganic mixture, the inorganic mixture is ball-milled to obtain an inorganic mixture powder, and the inorganic mixture powder is calcined at high temperature to obtain a molten salt material; A2, the molten salt material and ethanol are mixed at a solid-liquid ratio of 1:15-20 to obtain a mixture, and then the mixture is ultrasonically treated with an ultrasonic crusher to obtain a suspension, and the coating material is added to the above suspension, mixed and stirred at 100-200r / min at room temperature for 24h, and then washed with anhydrous ethanol and centrifuged to remove excess coating material to obtain a coated molten salt material; A3. The pH value of the plating solution is adjusted to 4.5-5.5, and the modified molten salt particles are added to the plating solution to carry out primary reaction and secondary reaction in sequence, and then vacuum dried at 120-130° C. to constant weight to obtain reinforced alloy powder.

5. An alloy roller according to claim 4, characterized in that: In step A1, the ball milling speed is 100-200 r / min, the ball milling time is 10-15 h, the high temperature calcination temperature is 450-500° C., and the high temperature calcination time is 30-60 min. In step A2, the coating material is polyvinyl pyrrolidone, the frequency of ultrasonic treatment is 1000-2000 Hz, the time of ultrasonic treatment is 30-60 min, and the mass ratio of the mixture to the coating material is 5:1-2.

6. The alloy roll according to claim 4, characterized in that: In step A3, the dosage ratio of the modified molten salt particles to the plating solution is 100g:10-20mL; the temperature of the primary reaction is 50-60°C, and the duration of the primary reaction is 30-60min; the temperature of the secondary reaction is 80-90°C, and the duration of the secondary reaction is 30-60min.

7. A surface strengthening treatment method for an alloy roll according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. The reinforced alloy powder and the binder are mixed evenly to obtain a powder, and the powder is evenly coated on the surface of the composite alloy roller, with a coating thickness of 0.3-0.5 mm, and the coating is naturally air-dried and heat-insulated to obtain a coated alloy roller; S2. The coated alloy roll is preheated to 100-200° C. to obtain a preheated alloy roll. The preheated alloy roll is fixed on a sample holder of a PRC-3000 fast axial flow CO2 laser and subjected to laser treatment to obtain an alloy roll.

8. The surface strengthening treatment method of an alloy roll according to claim 7, characterized in that: In step S1, the binder is polyvinyl alcohol, and the mass ratio of the reinforced alloy powder to the binder is 1:1; in step S2, during the laser treatment, nitrogen protection is used on the side, the laser spot diameter is 2 mm, the laser power is 1500-2000 W, and the laser scanning speed is 1500-2000 mm / min.

Citation Information

Patent Citations

  • Wear-resistant low-alloy high-speed steel composite roller and preparation method thereof

    CN114570903A